2020
DOI: 10.1063/5.0011270
|View full text |Cite
|
Sign up to set email alerts
|

Inertial effects on trapped active matter

Abstract: In this work, the dynamics of inertial (mass and moment of inertia) active Brownian particles trapped in a harmonic well is studied. This scenario has seen success when characterizing soft passive and active overdamped matter. Motivated by the variety of applications of this system, we analytically find the effect of translational and rotational inertia on the mean-square displacement (MSD), mean-square speed (MSS), swim, Reynolds, and total pressures of a system of inertial active Brownian particles subject t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…The understanding of these aspects requires a description taking into account the acceleration of the particles, in contrast with the one commonly employed to describe self-propelled systems. As recent studies have shown, inertia affects many properties of active particles, such as their pressure [13][14][15][16][17], transport properties [18,19], the stochastic energetics [20] and, even, anomalous responses to boundary driving [21]. Besides, inertial forces play an important role also at the collective level: i) affecting the clustering typical of active matter and, in particular, suppressing the phase-coexistence [22][23][24][25][26] and changing several features of the transition [27] ii) modifying some properties of dense phases of active matter [28], such as the active temperature in the homogeneous [29] and inhomogeneous phases [30].…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of these aspects requires a description taking into account the acceleration of the particles, in contrast with the one commonly employed to describe self-propelled systems. As recent studies have shown, inertia affects many properties of active particles, such as their pressure [13][14][15][16][17], transport properties [18,19], the stochastic energetics [20] and, even, anomalous responses to boundary driving [21]. Besides, inertial forces play an important role also at the collective level: i) affecting the clustering typical of active matter and, in particular, suppressing the phase-coexistence [22][23][24][25][26] and changing several features of the transition [27] ii) modifying some properties of dense phases of active matter [28], such as the active temperature in the homogeneous [29] and inhomogeneous phases [30].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the PAM both unifies ABPs and AOUPs and provides a crucial step towards more realistic modeling of overdamped (dry) active motion in general, which should in future work be employed to provide an improved fit of experimental swim-velocity distributions. Investigating the effect of the swim-velocity fluctuations could represent an interesting perspective for circle swimming [92][93][94][95][96][97] , systems with spatial-dependent swim velocity [98][99][100][101][102][103] , and inertial dynamics [104][105][106][107][108] even affecting the orientational degrees of freedom 109,110 . The generalization of PAM to these cases could be responsible for new intriguing phenomena which will be investigated in future works.…”
Section: Parental Active Modelmentioning
confidence: 99%
“…We study a two-dimensional system of N interacting active particles using the underdamped version of the Active Brownian Particles (ABP) model [39][40][41][42][43][44][45][46] . The particles are spatially confined in an annular container created by the presence of repulsive soft walls which will be described in the following.…”
Section: Modelmentioning
confidence: 99%